Ending the Stick and Embracing the Carrot: The Middle Way of Spin-Off Policy in Indonesian Islamic Banking - Sigit Pramono; Saiful Anwar; Adril Hakim; Aziz Budi Setiawan; Handi Risza; Gustofan Mahmud; Abdul Mujib Arijuddina (Universitas Ahmad Dahlan, 2026)
The implementation of the P2SK Law has triggered debate over the mandatory spin-off of UUS from BUK into BUS. This study examines the arguments from both sides to identify potential areas of consensus. It finds that poor communication, particularly on the